POLA INTERAKSI SOSIAL MASYARAKAT PADA ORGANISASI ISLAM NAHDLATUL ULAMA DAN MUHAMMADIYAH - Silvy Maulidia Izqi,; Subiyanto,; R. Samidi,; , Wahyu Jati Kusuma (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This research aims at the pattern of community social interaction that exists between the Islamic organizations Nahdlatul Ulama and Muhammadiyah in Karangdawa village, Margasari district, Tegal district. This research uses a qualitative research method that uses a field approach (field research) and this research design uses a descriptive design. Data collection techniques use observation, interviews and documentation. The results of this research are 1) the Islamic organizations Nahdlatul Ulama and Muhammadiyah in Karangdawa village which are structured and clear regarding their composition or order as evidenced by the running of the programs. 2) the pattern of social interaction of the people from the Islamic organization Nahdlatul Ulama and Muhammadiyah in Karangdawa village can be seen in everyday life, the interaction between the two is also seen when they are synergizing and working together in society, thus the social interaction between them forms a social process that is closer and then brings relationships. harmony in Karangdawa village. 3) The interaction of the two organizations is also influenced by driving factors including imitation, suggestion, identification, sympathy and self-introspection. And then the factors inhibiting social interaction are competition, contradiction and conflict.